SUSAN LARSON (ed.) - Comfort and Domestic Space in Modern Spain - Zubiaure, Maite (ZARCH, 2025)
SUSAN LARSON (ed.) Comfort and Domestic Space in Modern Spain University of Toronto Press, Toronto, 392 pp. Tapa dura. 100.00 Idioma: inglés ISBN-10‏: ‎ 1487529104 ISBN-13: ‎ 978-1487529109